Exposed Artificial Plate Covered With Perifascial Areolar Tissue as a Nonvascularized Graft. Issue 2 (February 2019) - Ito, Tomoyuki; Akazawa, Satoshi; Ichikawa, Yuichi; Yamamoto, Yusuke; Aoyama, Shohei; Kiuchi, Tomoki; Nakao, Junichi; Onitsuka, Tetsuro; Araki, Jun; Nakagawa, Masahiro
Abstract : Summary: Perifascial areolar tissue (PAT) is a loose connective tissue on deep fascia, such as on the groin, thigh, or temporal region, which has abundant vascular plexus and mesenchymal stem cells. Nonvascularized PAT grafts can survive even on hypovascular wound beds. Therefore, PAT grafting is a possible alternative to conventional flap surgery to cover exposed bone or artifacts. In this article, we describe 2 cases of PAT grafting for the treatment of skin ulcers with exposed bone and artificial plate after mandible reconstruction. After negative-pressure wound therapy, PAT was used to covering exposed artificial plate for both cases, and a skin graft onto the PAT graft was performed in 1 case. The ulcers improved in both cases without recurrence. The gold-standard treatment of intractable ulcers and fistulas with an exposed tendon, bone, or artifact is coverage by a well-vascularized skin flap. However, PAT grafting has advantages in similar situations, occasionally together with skin grafting and/or negative-pressure wound therapy, because it is technically simple and less invasive.